STABILITY ANALYSIS FOR SEED YIELD AND ITS COMPONENTS IN CORIANDER (CORIANDRUM SATIVUM L.) - M. S. DARVHANKAR; G. U. KULKARNI; V. V. BARASKAR; H. V. SOLANKI; P. A. VAVDIYA (The Bioscan, 2015)
The interaction between genotypes and environment (G x E) can influence the selection process and recommen- dation of coriander genotypes. The prime objective of this study was therefore to evaluate the influence of G x E interaction of coriander seed yield using stability parameters. Keeping of this principle thirty diverse genotypes of coriander were evaluated over three different dates of sowing during the Rabi season of the year 2011-2012. The data were recorded for ten different morphological characters. The environments, in which genotypes were grown, differed significantly for all the characters. Genotype x environment interaction were also significant for all the traits revealed differential response of the genotype to varying dates of sowing. Thirteen genotypes namely CGL-1, CGL-2, CGL-3, MKSM-1059, MKSM-1101, SINDHU, NDCOR-43, RCR-41, VDV/GL-2, AUSTRALIA, UD-401, MKSM-1116 and MKSM-1091 were found to be desirable and stable across the environments for seed yield. Thus, these genotypes could be included in the hybridization programme to converge the stability charac- teristic of seed yield for the development of a stable variety adapted to wide range of environments.